2014
DOI: 10.3746/jkfn.2014.43.11.1635
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antipruritic Activities of Ethyl Acetate Fraction from Diospyros lotus Leaves

Abstract: Diospyros lotus has been cultivated for its edible fruits, which are considered to have medicinal importance. The aim of this study was to evaluate the antioxidant and antipruritic activities of water-soluble, methanol extract, and ethyl acetate (EA) fractions from D. lotus leaves. The EA fraction showed the lowest IC50 vale (DPPH: 5.3 μg/mL, ABTS: 53.8 μg/mL). Therefore, we further investigated anti-inflammatory and antipruritic effects of the EA fraction. TNF-α production increased by PMA plus A23187 treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recent studies have found that the leaves have various activities, such as liver protection, 22 antiultraviolet damage, 23 and antipruritic. 24 Phenolic compounds isolated from the fruits and leaves of D. lotus, including gallic acid, methyl gallate, ellagic acid, kaempferol, quercetin, myricetin (Myt), myricetin 3-O-β-glucuronide, and myricitrin (Mytr), showed antioxidant activity. 17,25 However, there are no reports about nitrite scavenging and inhibition of NAs formation by D. lotus leaves and their active ingredients.…”
mentioning
confidence: 99%
“…Recent studies have found that the leaves have various activities, such as liver protection, 22 antiultraviolet damage, 23 and antipruritic. 24 Phenolic compounds isolated from the fruits and leaves of D. lotus, including gallic acid, methyl gallate, ellagic acid, kaempferol, quercetin, myricetin (Myt), myricetin 3-O-β-glucuronide, and myricitrin (Mytr), showed antioxidant activity. 17,25 However, there are no reports about nitrite scavenging and inhibition of NAs formation by D. lotus leaves and their active ingredients.…”
mentioning
confidence: 99%